Deteksi Mutasi Gen Gyrase A Porphyromonas Gingivalis Resisten terhadap Ciprofloxacin berdasarkan teknik Polymerase Chain Reaction - E.Rieuwpassa, Irene; Hatta, Mochammad (Jurnal Kedokteran YARSI, 2009)
One of resistance mechanisms to ciprofloxacin shown by bacterium Porphyromonas gingivalis isolated from periodontitis patients is mutations of genes through changes in DNA topoisomerase. Ciprofloxacin is an effective antimicrobial for Gram-negative bacteria effectively used for clinical infections treatment. The purpose of this research was to determine the gene mutation of P. gingivalis on periodontitis patients in relation to the resistance to ciprofloxacin by using disc diffusion and, followed by RFLP-PCR on P.gingivalis samples. Based on sensitivity tests by diffusion method, it was shown that the sensitive samples (n =13) had the highest inhibition zone diameter (mean= 25 mm), while the intermediate samples (n=1) was 19 mm. Examination using RFLP-PCR for 14 samples did not reveal any mutation of gyrase A gene.